Direct observation of dimethyl sulfide trapped by MOF proving efficient removal of sulfur impurities. Issue 8 (29th January 2020) - Morita, Masashi; Yonezu, Akira; Kusaka, Shinpei; Hori, Akihiro; Ma, Yunsheng; Matsuda, Ryotaro
Abstract : OMSs in HKUST-1 can strongly trap DMS even under humid conditions, which was directly proved by in situ single-crystal X-ray diffraction and Raman measurements. Abstract : Here, we report the adsorptive removal of trace amounts of dimethyl sulfide (DMS) using metal–organic frameworks (MOFs). Cu 2+ -based MOFs with open metal sites (OMSs), [Cu3 (btc)2 ] (HKUST-1), where btc = 1, 3, 5-benzenetricarboxylate, and without OMSs, [Cu2 (bdc)2 (dabco)] (Cu-JAST-1), where bdc = 1, 4-benzenedicarboxylate and dabco = 1, 4-diazabicyclo[2.2.2]octane, were investigated for the removal of DMS to compare their performance with that of Ag–Y zeolite, which is currently widely used in industry. HKUST-1 exhibited a considerably higher adsorption capacity for DMS than the other adsorbents, which was confirmed by breakthrough measurements. The adsorption state of DMS with HKUST-1 was directly revealed by single-crystal X-ray diffraction (SXRD) analysis and in situ Raman spectroscopy. In addition, it was shown that DMS can be removed by HKUST-1 even under humid conditions.